Economic recovery of cultural tourism village communities affected by Covid-19 using the SDGS program - Supriadi Acep; Supriyono; Nugraha Dadi Mulyadi; Gumelar Abih; Nur Muhammad (E3S Web of Conferences)
The Covid-19 pandemic has had an impact on the economy of cultural tourism village communities. The aim of this research is to formulate and analyze strategic steps for economic recovery of cultural tourism village communities through village government policies. This needs to be done considering the impact of the Covid-19 pandemic which has resulted in economic difficulties for the cultural tourism village community. The recovery of the community’s economy towards a new normal period needs to be carried out immediately so that it does not impact cultural tourism village destinations. This research uses a case study method in Rancakalong District, Sumedang Regency. Data collection techniques were obtained through literature studies and online interviews with village officials, tourism village managers and local communities. The analysis was carried out qualitatively by reducing the data resulting from research findings. The research results show that the economic recovery of cultural tourism village communities can be carried out with the policy of 1) Providing guidance to small business actors; 2) providing creative economy business capital loan assistance; and 3) training in marketing village cultural tourism products and destinations globally.